2016
DOI: 10.1002/chir.22572
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of C2 and C3 Symmetric (R)‐Phenylglycinol‐Derived Chiral Stationary Phases

Abstract: A C3 symmetric (R)-phenylglycinol N-1,3,5-benzenetricarboxylic acid-derived chiral stationary phase (CSP) and three C2 symmetric (R)-phenylglycinol CSPs were newly synthesized using o-, m-, and p-phthaloyl dichlorides. These CSPs were used to compare the resolution of 25 chiral samples using a previously reported 3,5-dinitrobenzoyl (R)-phenylglycinol-derived CSP. Even though all CSPs have the same chiral moiety, the C3 symmetric CSP showed the best resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 36 publications
0
22
1
Order By: Relevance
“…By using pyridine as the organic solvent in steps 2 and 3, the synthetic procedures of CSP 1 and 2 could be improved compared to the previously reported procedure . This modification reduced the reaction time and increased the amount of chiral selector introduced into the silica gel (the amount of loaded chiral selector of the previously reported CSP 1 was 0.167 mmol/g) . The crude intermediates 3c and 4c were not purified because some of the impurities could be removed in the course of silica gel washing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using pyridine as the organic solvent in steps 2 and 3, the synthetic procedures of CSP 1 and 2 could be improved compared to the previously reported procedure . This modification reduced the reaction time and increased the amount of chiral selector introduced into the silica gel (the amount of loaded chiral selector of the previously reported CSP 1 was 0.167 mmol/g) . The crude intermediates 3c and 4c were not purified because some of the impurities could be removed in the course of silica gel washing.…”
Section: Resultsmentioning
confidence: 99%
“…10 The results revealed that the (R)-phenylglycinol-derived C3symmetric CSP had a better resolution and separated more chiral samples compared to the other CSPs. 10 (S)-Leucinol, (S)-leucine, and (R)-phenylglycine derivatives were considered good candidates for improved chiral selectors of C3-symmetric CSPs. An easily synthesizable N-3,5-DNB-leucinol-derived CSP (DNBleu-ol), reported in 2003, showed better results compared to other aminoalcohol-derived CSPs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, even if the racemic mixture is separated from the selected column, without high selectivity, complete baseline separation is not quite achieved and the accuracy of the enantiomeric purity decreases. In a previous study, the chiral stationary phase (CSP), N ‐3,5‐dinitrobenzoyl(DNB)‐(R)‐phenylglycinol derived CSP (CSP 1), one of the representative amino alcohol‐derived Pirkle‐type CSP, was effectively used for π‐acidic, π‐basic, and aromatic chiral samples . 2,2,2‐Trifluoro‐1‐(9‐anthryl)ethanol (TFAE, S1) was separated from CSP 1 with an α value (separation factor) of about 1.16, but poor baseline separation (Rs: 0.82).…”
Section: Introductionmentioning
confidence: 99%
“…There are many preparation methods for chiral compounds, [1][2][3][4][5][6] but these methods often have some drawbacks, such as many processing steps, high cost, and low capacities. Since the advantages of solid membranes are high-throughput, energy-saving, pollution-free, low-cost, and easy operation, solid membrane technologies have been widely used in the desalination of seawater, wastewater treatment, chemical engineering, the medical field, metallurgy, etc.…”
Section: Introductionmentioning
confidence: 99%